Impacts of Adopting Improved Barley Varieties on Farmers’ Income in Ethiopia (American Journal of Economics and Business Innovation, 2024)
Improved agricultural technology adoption is vital in enhancing production, productivity, food security, and poverty reduction. This study assessed the level of income improvement as the result of adopting improved barley varieties for smallholder barley producers in Ethiopia. A multi-stage sampling method was followed to randomly select 18 districts, 42 kebeles, and 626 sample households from the potential barley-producing regions of Ethiopia, namely the Oromia, the Amhara, and the SNNP regions. The propensity score matching was estimated using logistic regression, and the kernel matching with a bandwidth of 0.1 was utilized to match 220 adopters with 402 non-adopters by rejecting two observations from adopters, and two observations from non-adopters. Finally, the treatment effect was estimated, and the result confirmed that farm households who adopted improved barley varieties got an extra income of birr 13,174.51 compared to non-adopter households. Therefore, agricultural policies and strategies in favor of the generation, dissemination, and adoption of improved farm technologies are recommended to take the lives of millions out of poverty and food insecurity.